What works? Regional effects of universities - Nicolas Bunde; Nina Czernich; Oliver Falck; Gabriel Felbermayr (EconPol Forum, 2022)
Universities exert a positive impact on the development of a region. They increase employment in high-tech and knowledgeintensive industries and raise long-term wages. Research results from universities are the basis for technological progress, new products, and start-ups. Framework conditions and institutional characteristics play an important role for such effects. Innovation ecosystems grow over years and decades. Therefore, higher-education policy must be long-term
Keywords: 330